A multiprotein complex that mediates translational enhancement in drosophila. - Nelson, M.R.; Luo, H.; Vari, H.K.; Cox, B.J.; Simmonds, A.J.; Krause, H.M.; Lipshitz, H.D.; Smibert, C.A. (Journal of Biological Chemistry, 2007)
Modulating the efficiency of translation plays an important role in a wide variety of cellular processes and is often mediated by trans-acting factors that interact with cis-acting sequences within the mRNA. Here we show that a cis-acting element, the Hsp83 degradation element (HDE), within the 3'-untranslated region of the Drosophila Hsp83 mRNA functions as a translational enhancer. We show that this element is bound by a multiprotein complex, and we identify components using a novel affinity-based method called tandem RNA affinity purification tagging. Three proteins (DDP1, Hrp48, and poly(A)-binding protein) are components of the HDE-binding complex and function in translational enhancement. Our data support a model whereby the HDE is composed of several cis-acting subelements that represent binding sites for trans-acting factors, and the combined action of these trans-acting factors underlies the ability of the HDE to stimulate translation.